The Effectiveness of Oil Essensiil Foot Massage Citronella of Lavender and Blood Pressure Hypertension Elderly Patients - Zaenal Amirudin; Suryo Pratikwo; Rr. Sri Sedjati (Poltekkes Kemenkes Semarang, 2014)
This study aims to determine the difference in effectiveness between the foot massage with lavender essential oils of citronella oil to decrease blood pressure in elderly hypertensive patients in Pekalongan City. This type of research is randomized pre-post test design with control